2014
DOI: 10.1037/a0037496
|View full text |Cite
|
Sign up to set email alerts
|

Adding an Internet-delivered treatment to an efficacious treatment package for opioid dependence.

Abstract: Objective To examine the benefit of adding an internet-delivered behavior therapy to a buprenorphine medication program and voucher-based motivational incentives. Method A block-randomized, unblinded, parallel, 12-week treatment trial was conducted with 170 opioid-dependent adult patients (mean age 34.3 years; 54.1% male; 95.3% white). Participants received an internet-based community reinforcement approach intervention plus contingency management (CRA+) and buprenorphine, or contingency management alone (CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(128 citation statements)
references
References 36 publications
5
123
0
Order By: Relevance
“…Christensen and colleagues (40) randomized 170 opioid-dependent individuals to buprenorphine with contingency management alone (maximum voucher value $997) or contingency management combined with the computerized Therapeutic Education system. The combined computerized therapeutic education system plus contingency management was associated with significantly better retention than contingency management alone through the 12-week trial (80% versus 64%) as well as significantly longer periods of abstinence (mean of 55 versus 49 days).…”
Section: Overview Of the Four Trials Showing No Benefit Of Adding Coumentioning
confidence: 99%
“…Christensen and colleagues (40) randomized 170 opioid-dependent individuals to buprenorphine with contingency management alone (maximum voucher value $997) or contingency management combined with the computerized Therapeutic Education system. The combined computerized therapeutic education system plus contingency management was associated with significantly better retention than contingency management alone through the 12-week trial (80% versus 64%) as well as significantly longer periods of abstinence (mean of 55 versus 49 days).…”
Section: Overview Of the Four Trials Showing No Benefit Of Adding Coumentioning
confidence: 99%
“…Those assigned to either form of CRA (therapist delivered or via TES) had significantly longer periods of continuous abstinence (8.0 weeks for therapist-delivered CRA and 7.8 for TES) compared with standard buprenorphine treatment (4.7 weeks) in this 23-week trial (Bickel et al, 2008). Subsequent trials of TES have indicated benefit of adding TES to standard methadone treatment (Marsch, Guarino, et al, 2014) as well as the benefits of the TES system itself in addition to contingency management in the context of buprenorphine maintenance treatment (Christensen et al, 2014). A recent multisite trial of TES plus prize based contingency management (Petry et al, 2005) (wherein participants earned chances to earn prizes for submitting drug free urine specimens or completing TES modules) was conducted in 10 outpatient settings with 507 drug-using individuals in a 12-week trial.…”
Section: The Promise Of Technologymentioning
confidence: 99%
“…Fluency training helps to ensure optimization for mastery of the cognitive-behavioral skills and information presented during computerized modules. Randomized clinical trials have assessed the efficacy of computer-delivered compared to therapist-delivered modules, finding that the Therapeutic Education System was associated with significantly greater rates of abstinence as well as significantly lower dropout rates (Bickel et al, 2008; Campbell et al, 2014; Christensen et al, 2014). Leveraging state-of-the-art technologies in the further development of behavioral economic interventions will allow for more frequent and accurate assessment as well expanding the reach for behavioral economic interventions.…”
Section: Trans-disease Processes and Therapeuticsmentioning
confidence: 99%